2013
DOI: 10.1007/s10096-012-1801-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among methicillin-resistant Staphylococcus aureus isolates from cancer patients in Saudi Arabia

Abstract: One hundred and twenty methicillin-resistant Staphylococcus aureus (MRSA) isolated from cancer and non-cancer patients in Saudi Arabia were investigated for antibiotic resistance, virulence determinants and genotypes. The majority of MRSA isolates from cancer (n = 44, 73.3 %) and non-cancer patients (n = 34, 56.7 %) were multi-resistant to more than four classes of antibiotics. Virulence gene profiling showed that all strains were commonly positive for adhesin genes, except ebps and bbp genes, which were not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
6
14
1
Order By: Relevance
“…In the present study, 10 different spa types were identified, among which spa type t037 was the most prevalent, accounting for 23.3% of the isolates. This spa type was reported in previous studies conducted in Iran (10), China (29), and Saudi Arabia (30). It is noteworthy to mention that the majority of isolates (81%) with spa type t037 were MRSA.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, 10 different spa types were identified, among which spa type t037 was the most prevalent, accounting for 23.3% of the isolates. This spa type was reported in previous studies conducted in Iran (10), China (29), and Saudi Arabia (30). It is noteworthy to mention that the majority of isolates (81%) with spa type t037 were MRSA.…”
Section: Discussionsupporting
confidence: 81%
“…Spa type t631 was the second frequent type in this study and also reported for the first time in Iran. In other studies, this spa type was reported with low frequency (45,49). It is interesting to note that all the t631 spa types in the present study were MRSA.…”
Section: Discussionsupporting
confidence: 67%
“…The ability of S. aureus to cause a spectrum of diseases both in humans and animals is due to a combination of bacterial virulence factors [6]. There are several virulence factors secreted by S. aureus including Panton-Valentine Leukocidin (PVL), protein A, toxic shock syndrome toxin 1 (TSST-1), and exfoliative toxins and several other toxins [3].…”
Section: Introductionmentioning
confidence: 99%
“…They may differ in the arrangement of chromosomal alleles, or the content of variable accessory genetic elements that confer certain resistance traits on the pathogen. Therefore, it is of prime importance to understand the genetic characteristics of these MRSA isolates which could be used to control these pathogens [6].…”
Section: Introductionmentioning
confidence: 99%